Analisis Viktimologi Terhadap Tindak Pidana Pencurian Kendaraan Di Tanjungpinang Kepulauan Riau - Sianturi, Michael (Universitas Pancasakti Tegal, 2022)
This paper will discuss the victimization analysis of the role of the victim in the occurrence of the crime of theft of two-wheeled vehicles with a case study of decision number: 29/Pid.B/2022/PN Tpg located in Tanjungpinang City. The background of this research is the crime of theft of property in this case two-wheeled vehicles with the aim of this research is to analyze how the role of the victim so that a crime occurs. The method used is descriptive analysis with secondary data sources. Theft is an act done intentionally to take other people's property against the law. This crime is classified as a crime against property that gives results and is classified as having a decent economic value for the perpetrators. This study will discuss victimization starting from the definition, scope, involvement, and perspective of the victim's responsibility. The conclusion is that crime does not necessarily arise from the perpetrator but the victim also provides an opportunity by leaving the motorbike key depending on the motorbike in a quiet and unsupervised yard.